Facilitators and barriers of Community Case management of Malaria implementation in Homabay, Busia and Kakamega Counties, Kenya - Sheila Lumumba; Albino Luciani; Bryson Sifuma; Dennis Kinyua; George Gikunda; Norah Ogutu; John Onyango; Diana Mukami; Colleta Kiilu; Saida Kassim; Yvonne Opanga; George Githuka (PLoS ONE, 2025)
Background Community Case management of malaria (CCMm) is a strategy used in malaria-endemic areas to reduce malaria morbidity and mortality. CCMm involves providing malaria diagnosis and treatment within the community by trained community health volunteers (CHVs). While evidence suggests CCMm is effective in combating the disease burden at the community level, it isn’t without challenges. This study assesses facilitators of and barriers to uptake of CCMm. Methods This cross-sectional study employed a mixed methods approach. Quantitative data was collected using a household questionnaire targeting 528 participants, while qualitative data was collected using 4 focused group discussions and 20 key informant interviews. Quantitative data was cleaned, coded, and analyzed using STATA version 14. Qualitative data was transcribed, and the data was analyzed using NVIVO version 10. Results The study found that 72% of households had received a service on Malaria, and this was consistent across all counties (Busia 75%, Homabay 72%, Kakamega 71%). 62% of respondents considered CHVs a regular source of healthcare, with approximately 85% of the population being satisfied with the services offered by CHVs. Key initiatives that improved the effectiveness of CCMm included sensitization on malaria causes and preventive measures, training of CHVs on the management of malaria, and empowerment of CHVs who can utilize rapid tests to diagnose malaria at the household level. The facilitators of CCMm included the availability of malaria commodities, a functional referral system, and support supervision from the Community Health Assistants (CHA) and Health Management Teams. Barriers that hindered the implementation of CCMm included myths and misconceptions surrounding the use of mosquito nets, stock outs of malaria commodities such as the Malaria Rapid Diagnostic Test (mRDT) kits and antimalarials, and inaccessible roads into the communities. Conclusion In spite of great strides in CCMm initiatives to reduce malaria-related Morbidity and mortality, some of the barriers underpinning its effectiveness remain unaddressed. Continuous training for CHVs, sustained availability of commodities for testing and treating malaria, and incentives are essential for the success and sustainability of CCMm initiatives.